Immunotherapy with Hymenoptera venom in a child with anaphylaxis - Falcão,Inês (2021)
Abstract Systemic reactions to hymenoptera venom in childhood are uncommon, comprising less than 1% of cases. The prevalence proves higher in adults, encompassing 0.3−8.9%. Anaphylaxis forms the most severe of all allergic reactions and can be fatal. Specific immunotherapy based on hymenoptera venom is the only treatment that prevents moderate-to-severe systemic reactions. Due to immunotherapy safety and effectiveness, this treatment is indicated during childhood in cases of grade II and III systemic reactions. The authors describe the clinical case of a fourteen-year-old male patient, son of a beekeeper, who was followed in the Allergy and Clinical Immunology Department due to anaphylaxis to hymenoptera venom and was under immunotherapy to Apis mellifera venom since the age of nine, besides complying with measures to evade hymenoptera.